Social activism in Czech hardrock music in 1970s and 1980s - Zemanová, Zuzana (Bohemica Olomucensia, 2017)
After 1969 in Czechoslovakia rock music was regarded as undesirable in general. Nevertheless, we have found many examples of social activism in lyrics by Czech hardrock groups and singers, which were consensual with the official political line. The paper is focused especially on songs written by Ladislav Vostárek for group Katapult and František Ringo Čech for singer Jiří Schelinger. Their lyrics were didactic primarily to young people; warning against alcoholism, speeding, crime; appeal to protection of environment etc. Social topics like these were popular between musicians both professional and amateur, because the communist regime accepted them as 'activistic' enough and the authors were lucky that they avoided strictly political area. Consequently, this kind of lyrics contributed to better position of rock music in Czechoslovakia.
Keywords: hardrock music; lyrics; social activism; 1970s; 1980s; Czechoslovakia